SEMANTIC CLASSIFICATION OF THE VERBS IN THE NORTH AMERICAN AREA OF THE ENGLISH LANGUAGE - L.V. Mykhailyuk (Vasyl Stefanyk Precarpathian National University, 2015)
The article deals with the problem of semantic classification of the verbs of the North American continent. 60 verbs marked in the dictionaries (Hornby, Webster, Gage) as British, American, Canadian have been chosen for the investigation. The classification of verbal lexemes according to their semantic meaning suggested by A.A. Ufimtseva has been taken for the basis of this research. According to this classification all the verbs fall into two groups: lexemes of active action and lexemes of non-active action.